Modeling the term structure - Christoph Memmel; Lotta Heckmann (Deutsche Bundesbank, 2025)
Based on an analysis of changes in the yields of German government bonds, we propose a simple model for the term structure of interest rates and show empirically that this model with two parameters (relating to the interest level and slope of the term structure) fits empirically well the data for a change horizon of one year or longer, especially in the low interest environment, and give examples for applications. In addition, we provide closed-form solutions for some interest bearing instruments and give a new interpretation for the convexity when this linear model for the term structure is used.
Keywords: G21; 330; Term Structure of Interest Rates; Duration and Convexity; Common Factors; Government Bonds